Chromone: A valid scaffold in medicinal chemistry - Gaspar, Alexandra (2015)
Chromones are a group of naturally occurring compounds that are ubiquitous in nature, especially in plants. The word chromone is derived from the Greek word chroma, meaning “color”, which point out that many chromone derivatives can exhibit a diversity of colors.